Privately Held or Publicly Owned? Large Shareholders and Corporate Control - Toukan, Amjad (2014)
This paper examines the decision to go public in the presence of large and dispersed shareholders. The decision to go public and the shape of the ownership structure itself depend on the particular combination of concentrated and dispersed ownership that maximizes the initial owners’ wealth. Owners/managers and large shareholders exert costly efforts to increase their share of the value of the public firm. The respective shares and the listing decision are affected by the efficiency of the judiciary and law enforcement system.